Pengaruh Kompensasi Dan Motivasi Kerja Terhadap kinerja Karyawan pada CV Andriel Textile Tanah abang Jakarta Pusat: The Effect of Compensation and Work Motivation on Employee Performance at CV Andriel Textile Tanah abang Central Jakarta - Zebua, Iman Citra; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstracts – This study aims to investigate the impact of compensation and job motivation on employee performance at CV Andriel Tekstil in Tanah Abang, Central Jakarta. The background to the issue shows that in the competitive textile industry, efficient human resource management (HRM), including compensation and motivation, is crucial for achieving company goals and maintaining employee productivity. Preliminary observations indicate employee dissatisfaction with the compensation provided, as well as low work discipline, which could potentially reduce performance. The research method used a quantitative approach with an associative method to identify the relationship between the variables. The sample comprised 61 respondents, selected using a saturation sampling technique. Data were analysed using multiple regression analysis to determine the influence of compensation and job motivation on employee performance. The results of the study show that compensation and work motivation together have a positive and significant influence on employee performance. However, in isolation, only job motivation was found to have a significant impact on performance, while compensation did not. These findings emphasise the importance of work motivation as a key factor in improving employee performance at CV Andriel Tekstil. Keywords: Compensation, Work Motivation, Employee Performance